2018
DOI: 10.1249/mss.0000000000001480
|View full text |Cite
|
Sign up to set email alerts
|

Maximal Exercise Alters the Inflammatory Phenotype and Response of Mononuclear Cells

Abstract: These findings demonstrate that acute maximal exercise elicits a proinflammatory phenotype of isolated monocytes exposed to LPS and highlight potential mechanisms that will help elucidate the role of acute and chronic exercise on the innate immune response of circulating monocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 38 publications
5
15
0
Order By: Relevance
“…So, it makes sense that by reducing the gene expression of the TLR-4 and then reducing the expression of its downstream molecules in the signaling pathway, such as IRF3 and NF-κB, the expression of TNFα as the end product of this pathway will also decrease. A reduction in TNFα serum levels has been shown following long-term protocols [39,[46][47][48], which is in line with our study, while others have reported increased or unchanged levels [22,34,49]. Studies have shown that in the presence of IFNγ macrophages shift their phenotype toward M1 and produce proinflammatory cytokines, including IL-12, TNF-α, and IL-1β [50,51].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…So, it makes sense that by reducing the gene expression of the TLR-4 and then reducing the expression of its downstream molecules in the signaling pathway, such as IRF3 and NF-κB, the expression of TNFα as the end product of this pathway will also decrease. A reduction in TNFα serum levels has been shown following long-term protocols [39,[46][47][48], which is in line with our study, while others have reported increased or unchanged levels [22,34,49]. Studies have shown that in the presence of IFNγ macrophages shift their phenotype toward M1 and produce proinflammatory cytokines, including IL-12, TNF-α, and IL-1β [50,51].…”
Section: Discussionsupporting
confidence: 91%
“…Although the acute protocols have not significantly changed TLR4 mRNA levels, the increase in the duration of training protocols appears to shift these results toward a reduction of TLR4 levels [33]. According to human studies, both acute, though not all, types of exercise (HIIT) [23] and long-term interventions downregulate TLR4 in the obese, healthy, and type 2 diabetes subjects [24,34,35]; this corresponds with the findings here. On the contrary, TLR4 levels have remained unchanged or elevated after RT and aerobic protocols [36,37].…”
Section: Discussionsupporting
confidence: 83%
“…It was demonstrated that acute exercise induces several systemic proteins, including apolipoproteins and immunological mediators, that may be involved in immunosurveillance during and after exercise bouts 24 . However, some exercise modalities, such as exhaustive exercise that induces higher degrees of muscle damage and systemic stress response, may induce a greater pro-inflammatory response and activation of peripheral leukocytes that become deregulated and detrimental to health 9 , 25 .…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, there was a 20% decrease in the relative proportion of CD14 ++ CD16 − monocytes in these subjects. Similarly, Slusher et al [52] reported that maximal treadmill exercise performed by 25 healthy men resulted in a 7.7% decrease in the relative percentage of CD14 ++ CD16 − monocytes, and 15.6% and 43.1% increases in relative percentages of CD14 ++ CD16 + and CD14 + CD16 ++ monocytes, respectively. Interestingly, there was decreased TLR4 expression on CD14 ++ CD16 − and CD14 ++ CD16 + monocytes but not in CD14 + CD16 ++ monocytes.…”
Section: Exercise Modulates Monocyte Subsetsmentioning
confidence: 94%